Prevalence of chronic pain in developing countries: systematic review and meta-analysis. (November 2019) - Sá, Katia Nunes; Moreira, Larissa; Baptista, Abrahão Fontes; Yeng, Lin Tchia; Teixeira, Manoel Jacobsen; Galhardoni, Ricardo; de Andrade, Daniel Ciampi
Abstract : Abstract: Chronic pain (CP) is prevalent worldwide. Current reports on its prevalence in developing countries are heterogeneous, and to date, there is no quantitative synthesis providing a general estimation of its magnitude in the developing world. The goal of this study was to estimate the pooled prevalence of CP in the general population in developing countries. This was a PROSPERO-registered CRD42019118680 systematic review including population-based cross-sectional studies on CP from countries with ⩽0.8 human developing index. We calculated prevalence using both random effects and fixed effects. Heterogeneity was calculated by the Cochran Q test and the I 2 statistic. Publication bias was evaluated by visual inspection of the Egger funnel plot, as well as by the Begg rank test and the Egger linear test. Sources of heterogeneity were also explored in subgroup analyses. Twelve studies with a total of 29, 902 individuals were included in this meta-analysis, of which 7263 individuals were identified with CP. The overall pooled prevalence of CP after correction for publication bias was 18% (95% confidence interval: 10%–29%), the sample presenting significant heterogeneity (I2 = 100%, P < 0.001). Subgroup analyses demonstrated that year of publication and the adopted threshold for pain chronicity could partially explain the observed heterogeneity ( P < 0.05). The proportion of individuals with CP in the general population of developing countries was 18%. However, reports of prevalence have high variability, especially related to year of publication and the threshold level adopted for pain chronicity. Abstract : Supplemental Digital Content is Available in the Text.